Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
[tex]x=6, x=-4[/tex]
Step-by-step explanation:
1) Let's solve this quadratic equation by factorizing. We need to find two numbers that multiply to -24 and add up to -2 simultaneously. If we pull out the factors of -24, two of them will be -6 and 4, which multiply to -24 as well as add up to -2.
3) Write [tex]-2x[/tex] as a sum.
[tex]x^2-6x+4x-24=0[/tex]
Now, we can factor them out by grouping.
[tex]x^2-6x+4x-24=0\\x(x-6) + 4(x-6)=0[/tex]
Since, [tex]x -6[/tex] is common in both of the factors, we only take one of the [tex]x -6[/tex] along with [tex]x[/tex] and [tex]4[/tex] and all equated to 0.
[tex](x-6)(x+4) = 0[/tex]
Solve for x: [tex]x-6=0[/tex]
[tex]x=0+6\\x=6[/tex]
Solve for x: [tex]x+4=0[/tex]
[tex]x=0-4\\x=-4[/tex]
Therefore, our solutions to this quadratic equation are [tex]x=6, x=-4[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.